Best Animated Film Semi Finalist Academy Award ® Qualifying/BAFTA Qualifying/Canadian Screen Award Qualifying - Sofokleous, Konstantina (My University, 2026)
Flickers' Rhode Island International Film Festival. USA
Keywords: Arts and entertainment